2014
DOI: 10.1642/auk-13-164.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid radiation and hybridization contribute to weak differentiation and hinder phylogenetic inferences in the New World Mallard complex (Anasspp.)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 30 publications
(75 citation statements)
references
References 98 publications
3
71
1
Order By: Relevance
“…ybp = 632,305, range = 166,166–2,076,004 ybp) data sets. Our estimated divergence times between black ducks and wild mallards are on average greater than previously suggested (180,000 ybp (95% CI = 100,000–400,000 ybp); Lavretsky, Hernández Baños, et al, ), which may be due to the much smaller set of used loci (17 nuclear introns) and samples (25 per species) analysed previously. Finally, we recovered a relatively low migration rate of approximately two to three migrants per generation whether analysing historical (1.87 migrants per generation, range = 0.04–8.44 migrants per generation) or contemporary (2.82 migrants per generation, range = 0.21–9.72 migrants per generation) data sets.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…ybp = 632,305, range = 166,166–2,076,004 ybp) data sets. Our estimated divergence times between black ducks and wild mallards are on average greater than previously suggested (180,000 ybp (95% CI = 100,000–400,000 ybp); Lavretsky, Hernández Baños, et al, ), which may be due to the much smaller set of used loci (17 nuclear introns) and samples (25 per species) analysed previously. Finally, we recovered a relatively low migration rate of approximately two to three migrants per generation whether analysing historical (1.87 migrants per generation, range = 0.04–8.44 migrants per generation) or contemporary (2.82 migrants per generation, range = 0.21–9.72 migrants per generation) data sets.…”
Section: Resultscontrasting
confidence: 75%
“…Trimmomatic (Bolger, Lohse, & Usadel, ) was used to trim or discard poor quality sequences. The Burrows Wheeler Aligner v. 07.15 (bwa; Li & Durbin, ) program was used to index and align per sample sequences to our reference—comprised of initial ddRAD sequences used to build the capture array and a consensus mtDNA sequence of mallards and black ducks (Lavretsky, Hernández Baños, & Peters, ; Lavretsky, McCracken, et al, )—using optimized parameters as described in Schubert et al (; ‐T 25 ‐I 1024). Due to known postmortem degradation effects on DNA, we used MapDamage v 2.0 (Jónsson, Ginolhac, Schubert, Johnson, & Orlando, ) to rescale the base scores of historical samples based on patterns of DNA fragmentation and cytosine deamination.…”
Section: Methodsmentioning
confidence: 99%
“…Next, to visualize patterns of differentiation across the genome, pairwise per locus Φ ST values were calculated in the r package PopGenome (Pfeifer et al, ), and plotted in excel by chromosomal position (i.e., Manhattan plots). BayeScan v. 2.1 (Foll & Gaggiotti, ), which has relatively low rates of false positives (<1%) for populations with low overall differentiation (Pérez‐Figueroa, García‐Pereira, Saura, Rolán‐Alvarez, & Caballero, ), as is observed in the NW “mallard” radiation ( Φ ST estimates range from 0.011 to 0.043; Lavretsky, Hernández Baños, et al, ), was used to test for outlier loci. BayeScan employs a reversible‐jump MCMC method by calculating a posteriori probability models with and without selection across loci.…”
Section: Methodsmentioning
confidence: 99%
“…Among the monochromatic species, black ducks have the highest rates of hybridization and introgression with mallards (Lavretsky, Janzen, & McCracken, ), and previous studies have suggested either that the two forms are conspecific (Ankney et al, ), or that black ducks have suffered a complete breakdown of their genetic distinctiveness (Mank, Carlson, & Brittingham, ). Although the frequency of mixed pairs and hybrid individuals remains uncertain (Heusmann, ; Johnsgard, ; Kirby, Reed, Dupuis, Obrecht, & Quist, ), black ducks and mallards are genetically indistinguishable based on allozymes (Ankney et al, ), microsatellites (Mank et al, ), and sequence data from a limited number of mitochondrial and nuclear genes (Johnson & Sorenson, ; Lavretsky, Hernández Baños, & Peters, ; Lavretsky, McCracken, et al, ; McCracken et al, ). ddRAD‐seq methods, however, have provided sufficient genomic coverage and allele frequency differences to identify population structure, hybrid individuals, founder events, and genomic regions putatively under divergent selection between mallards and Mexican ducks (Lavretsky et al, ), between the two mottled duck subspecies (Peters et al, ), and more recently between mallards and black ducks (Lavretsky et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among these lineages, the genus Anas (i.e. the dabbling ducks) seems particularly predisposed for global radiations (Johnson and Sorenson , Proches and Ramdhani , Lavretsky et al ), which is likely attributable to their vagile tendencies. Within the genus Anas , the blue‐winged duck complex, named after their prominent blue wing patch, inhabits all continents except Antarctica and comprises six species, including the northern shoveler A. clypeata , the red shoveler A. platalea , the Cape shoveler A. smithii , the Australasian shoveler A. rhynchotis , the blue‐winged teal A. discors , and the cinnamon teal A. cyanoptera .…”
mentioning
confidence: 99%